The book of the kings of Egypt - Budge, E.A. Wallis Sir, 1857-1934. (Kegan Paul library of ancient Egypt., 2005)
Contains illustrations of the hyroglyphics used to chronicle the Egyptian lineage of kings. This book provides an explanation of the Egyptian Pharaohs, Ptolemies and Roman Emperors. It starts at the Twentieth Dynasty and ends with the Thirtieth, and includes the listings of the Macedonians and Ptolemies, Emperors and the Kings of Napata and Meroe.